IDENTIFICATION OF RACIAL AND ETHNIC DISCRIMINATION ACCORDING TO LAW NUMBER 40 OF 2008 AND DISCRIMINATION WOMEN ACCORDING TO LAW NO. 7 OF 1984 IN CIVIL CODE - Dardiri Hasyim (JURNAL HUKUM DE'RECHTSSTAAT, 2018)
This research attempts to find forms of discrimination in the Act No. 40 of 2008, Act No. 13 of 2003, as well as Act No. 7 of 1984, and compare with Civil Code. Research using the method of librarianship. The results showed there are 19 articles in the Civil Code which is discriminatory.  In the meantime there are 6 forms of discrimination in the Act No. 40 of 2008; and 17 form in Act No. 7 of 1984.